Hubungan Terpaan Tayangan Youtube Raditya Dika dengan Minat Belajar Finansial Komentator - Rofiq Rifansyah; Zulfebriges (UNISBA Press, 2022)
Abstract. Along with the development of an information and communication technology, then this is also followed easily and quickly that information is obtained so that a new media is formed. Youtube is a website that facilitates its users to share videos uploaded by various parties. The research